(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Pantai Baru is one of the beaches on the southern coast of Bantul Regency, Yogyakarta Special Region. The construction of the Pandansimo Bridge paved the way for the development of Pantai Baru. On the other hand, the physical conditions and human behavior in Pantai Baru indicate high vulnerability to multiple disasters such as tsunamis, abrasion, tidal flooding, and sea intrusion. The study employed a qualitative method, integrating the concept of Integrated Coastal Zone Management (ICZM) and an ecological approach. This study aims to examine the coastal tourism area management model based on disaster mitigation by identifying key area characteristics, land use patterns, and disaster risks, with the goal of designing a safer and more sustainable area management model. The result of the modeling is the Pantai Baru Tourism Area Management Model based on disaster mitigation through integrated sustainable zoning. This model divides the area into three main zones: the Conservation Zone (0-100 meters) as a natural green belt; the Economic Zone for tourism facilities (swimming pool, food stalls, ATV Track); and the Parking and Support Zone (PLTB, conservation office, mosque, and souvenir shop) which pays attention to user circulation and disaster evacuation circulation. In addition to structural mitigation, this arrangement emphasizes the importance of non-structural mitigation through community education and multi-stakeholder collaboration. This model is expected to increase regional resilience to disasters, support sustainable tourism growth, and reduce conflict and socio-economic risks.